Soil fauna diversity and chemical stressors: a review of knowledge gaps and roadmap for future research. Issue 6 (23rd February 2021) - Beaumelle, Léa; Thouvenot, Lise; Hines, Jes; Jochum, Malte; Eisenhauer, Nico; Phillips, Helen R. P.
Abstract : Soils harbour highly‐diverse invertebrate communities that play important roles for ecosystem services, including the mitigation of environmental pollution. Chemical stressors, such as pesticides, pharmaceuticals and metals, are being increasingly spread into ecosystems due to human activities. While it is crucial to predict the consequences of chemical stressors for soil biodiversity, chemical toxicity is often assessed using individuals or populations in laboratory cultures. There has been no systematic evaluation of the evidence documenting the impacts of chemical stressors on diverse, natural soil communities. Here, we use a comprehensive literature review of 274 studies to evaluate the current state of knowledge about the effects of chemicals on soil fauna communities. Most research has had limited spatial scope, with noteworthy gaps in the regions that are potentially the most threatened by soil pollution (Southern Hemisphere). Furthermore, reports generally were constrained to a few emblematic soil fauna groups (nematodes, collembola and earthworms) and chemical stressors (metals). Future research should address biases in spatial distribution of studies, as well as the taxonomic groups and chemical compounds considered. Specifically, emphasis on indirect effects mediated by species interactions, ecosystem functioning and interactive effects of stressors and climate change, currently lacking in the literature, is needed to improve soil‐biodiversity conservation and restoration efforts, as well as predictions of global diversity change.